Cognitive ability and games of school choice - Christian Basteck; Marco Mantovani (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
We take school admission mechanisms to the lab to test whether the widely-used manipulable Boston-mechanism disadvantages students of lower cognitive ability and whether this leads to ability segregation across schools. Results show this is the case: lower ability participants receive lower payoffs and are over-represented at the worst school. Under the strategy-proof Deferred Acceptance mechanism, payoff differences are reduced, and ability distributions across schools harmonized. Hence, we find support for the argument that a strategy-proof mechanisms 'levels the playing-field'. Finally, we document a trade-off between equity and efficiency in that average payoffs are larger under Boston than under Deferred Acceptance.
Keywords: C78; C91; D82; I24; 330; laboratory experiment; school choice; strategy-proofness; cognitive ability; mechanism design